Transferencia tecnológica: investigación y desarrollo, implementación industrial - Zúñiga Muñoz, Damián (2009)
Technology transfer is the process of sharing of skills, knowledge, technologies, methods of manufacturing, samples of manufacturing and facilities among governments and other institutions to ensure that scientific and technological developments are accessible to a wider range of users who can then further develop and exploit the technology into new products, processes, applications, materials or services. It'll be shown a synthesis about the real situation of Ecuador in regard of investigation and Technological Development Centers, which and how many articles are released each year.